Faktor-Faktor yang Berhubungan dengan Kinerja Kader Tuberkulosis di Kecamatan X: Studi Literatur - Ranny Tien Subarkah; Miftahul Falah; Ai Sukmawati (PT PUSTAKA CENDEKIA GROUP, 2025)
Tuberculosis (TB) remains a major global public health problem, including in Indonesia, which ranks second worldwide in terms of TB burden. One of the key efforts in TB control is improving the Case Detection Rate (CDR), which largely depends on the role and performance of TB cadres in the community. However, the performance of TB cadres is influenced by various factors originating from both individual characteristics and the work environment. This study aims to describe the factors associated with the performance of Tuberculosis (TB) cadres. The research method employed was a literature review by examining textbooks and three relevant national journal articles. Literature searches were conducted through Google Scholar using keywords related to TB cadre performance and its influencing factors. Data analysis was carried out using a descriptive narrative approach by comparing and synthesizing the findings of the reviewed studies. The results of the literature review indicate that the performance of TB cadres is influenced by several key factors, including competence, length of service, age, motivation, attitude, as well as organizational factors such as leadership and support from primary healthcare center managers. Cadres with good competence, sufficient work experience, high motivation, and positive attitudes tend to demonstrate better performance in TB case detection and patient treatment assistance.